Pengaruh Terapi Sholawat Terhadap Heart Rate, Respiration Rate, dan Saturasi Oksigen pada Bayi BBLR Di Ruang NICU : Case Report - Farida Salwa Azizah; Falasifah Ani Yuniarti; Rina Prawati (An-Najat, 2024)
LBW is one of the main factors in increasing infant mortality. LBW is a baby with an absolute birth weight of less than 2,500 grams regardless of age as measured 1 hour after birth. The sound of prayer provides a feeling of calm and relaxation, thus increasing oxygen saturation and reducing the frequency of heart rate and respiration which results in the body's metabolism becoming effective and efficient to support the growth and development of LBW neonates to catch up.  the research used in the intervention is a case report using the method intervention. This research was conducted in the NICU room at Tjitrowardojo Regional Hospital, Purworejo, 2-6 May 2024. Therapy was given once a day with a duration of 30-40 minutes for five consecutive days. After giving therapy, the heart rate, respiration rate and oxygen saturation are again measured on an observation sheet.  Providing prayer therapy intervention within 30 minutes for five days, the results showed a decrease in the average heart rate of respondents from 162.8 x / minute to 160.6 x / minute resulting in a decrease of 2.6 x / minute, there was a decrease The average respiratory rate in respondents was from 64.4x/minute to 62.4x/minute, resulting in a decrease of 2x/minute. Other changes also occurred in the oxygen saturation value from 89% on the first day of measurement and to 97% after intervened for five days of intervention.  Sholawat therapy has a positive influence on the patient's heart rate, respiration rate and oxygen saturation.